Colombian researchers tell us how to obtain bioproducts from coffee wastes (REVISTA SAYWA, 2024)
In this article, the student Maria Fernanda Muñoz Gonzalez presents an overview of the production of biogas from coffee pulp in Colombia, specifically in the department of Huila, in the year 2021. She shows the results of a previous study, the link to which can be obtained in this publication. The results presented by the authors show a surprising efficiency. They underline the relevance of biogas production in the Colombian context and point out an important problem: despite its successful production, biogas is often mixed with gasoline, which reduces its positive impact on the environment.
Keywords: Biogas; Ethanol; Coffe; Bioethanol; Article review